Plasma parameters at nanosecond breakdown and capillary discharge in a solid insulator - Barakhvostov, S. V.; Muzyukin, I. L. (Technical physics, 2009)
The subject of investigation is the energy-mass composition of a plasma resulting from the breakdown of KCl single crystals and from discharges in capillaries produced by the breakdown of KCl and high-pressure polyethylene samples. The plasma flux formed by the head of the discharge channel in KCl is found to be much less intense than the plasma flux due to the capillary and surface discharges. Also, the first breakdown of KCl does not produced multiply charged ions of the related material. It is revealed that the energies and charge numbers for the capillary and surface discharges are close to each other.